Analisis Srtrategi Bisnis Dalam Upaya Meningkatkan Profitabilitas UMKM Aspikmas Kabupaten Banyumas - Putri, Puspita Lianti; Widadi, Budi (LPPM Universitas Bina Sarana Informatika, 2024)
MSMEs are believed to be the main driver of the country's economy. On the other hand, MSMEs also have various limitations and oppose economic globalization due to weak financial resources and competitiveness. Most MSME owners do not have enough knowledge about how to develop a larger business (scale-up). Having a planned business strategy will help MSMEs increase product sales and increase profits. The aim of this research is to formulate, analyze and describe MSME business development strategies by looking at strengths, weaknesses, threats and opportunities and determining appropriate and accurate strategies to increase profitability. The research method used is a qualitative descriptive research method. The data used in this research are primary and secondary data. Data collection techniques through observation, interviews, documentation and distribution of questionnaires to Aspikmas MSMEs. The data analysis used in this research is SWOT analysis (Strength, Weakness, Opportunity and Threat). The results of this research show that an effective strategy based on SWOT Matrix Analysis and the Cartesian SWOT diagram produces an SO (Strength-Opportunity) strategy in quadrant 1, supporting Growth Oriented Strategy.